Pelibatan Private Military Company dalam Misi Perdamaian di Afganistan oleh PBB di Tahun 2014 - Prasetyo, Cahyo Tri; Albayumi, Fuat; Hara, Abubakar Eby (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
The level of security in Afghanistan has started to deteriorate since American military activities began. This is because the fight between the United States and the Taliban organization is causing an increasing number of civilian deaths. The United Nations (UN) is now involved in settling the conflict in Afghanistan as a result of the escalating conflict conditions there. In addition to deploying troops from member nation contingents, the UN also enlists the aid of a Private Military Company (PMC) to help carry out the peace mission in Afghanistan. However, International organization role theory and rational choice theory are both used in this Article. Keyword : UN, PMC, Afganistan